Stability and propagation of the high field side high density front in the fluctuating state of detachment in ASDEX Upgrade. (August 2017) - Manz, P.; Potzel, S.; Reimold, F.; Wischmeier, M.; Team, ASDEX Upgrade
Highlights: Dynamics of X-point fluctuations are studied via time-delay-estimations. A mechanism for fluctuations appearing during high-field-side detachment is proposed. The mechanism relies on the perpendicular neutral flux and geometrical constrains. Abstract: During detachment a structure of strongly enhanced density develops close to the inner target. Its dynamics is approximated by those of radiative fluctuations appearing at a similar position and studied by means of a time-delay-estimation technique in the ASDEX Upgrade tokamak. Compared to theory the dynamics can be described as follows: at increasing density the ionization front moves upstream to reduce ionization radiation in order to balance the increased recombination radiation. The recombination zone stays close to the target strike point. The parallel motion of the ionization front is determined by the perpendicular neutral motion. The divertor nose constitutes an obstacle for the perpendicular neutral flux from the target to the region above the X-point. Passing into this shadow the neutral flux above the X-point is strongly reduced, the ionization front fades away and the heat flux from upstream can increase the temperature in the recombination region, subsequently reducing recombination and reforming an ionization front below the X-point. A cyclic reformation of the ionization front propagating from below to above the X-point occurs leading to a fluctuation as observed in the experiment.